Developing entrepreneurship training curriculum based on Tawhidic paradigm and legal principles: a case study of Malaysia - Anor Salim, Farah Akmar; Maidin, Ainul Jaria; Mhd. Sarif, Suhaimi; Zainudin, Dolhadi (Scientific Publishing House, 2019)
The importance of legal literacy in conducting business dealings has long been argued by the academics. Besides aiming for profit, entrepreneurial activities are important in meeting the social obligations of the government to ensure the development of a resilient economy. Business schools are required to promote integrated curriculum to ensure entrepreneurs will not only be able to identify business opportunities supported by required management skills. The integrated curriculum besides providing students with the ability to comprehend the key business disciplines will also need to nurture the humanistic skills, ethics and values. The incorporation of these elements will help create entrepreneurs with civic-mindedness, excellent interpersonal communication and leadership skills as well as be resilient. This paper singles out the ideology in promoting integrated curriculum for entrepreneurs training in the Malaysian context particularly the importance of inculcating legal knowledge to ensure the entrepreneurs will manage their activities within the permitted limits of the Malaysian law and global requirements. A comprehensive set of questionnaire containing 68 questions were administered to 543 entrepreneurs using convenience sampling. The rational of the practice of selecting local entrepreneurs as a sample for the study is to obtain their opinions on the relevant skills needed in managing their business. This can help identify aspects that can be incorporated to improve the current entrepreneur’s training curriculum. The survey revealed that inculcating Islamic principles and ethics in entrepreneur's activities can increase their credibility in conducting business with others besidesbeing resilient in developing the business (concept of taqwa). The study provides significant information to the academic and business community including private corporations and governments on the essential elements that need to be incorporated in conducting business. Finally, the study concludes with proposing the important aspects to be incorporated in the entrepreneurs training curriculum in Malaysia specifically the Muslim world in general.